Epidemiology of Neisseria gonorrhoeae Gyrase A Genotype, Los Angeles, California, USA - Ashima A. Bhatti; Lao-Tzu Allan-Blitz; Mariana Castrejon; Romney Humphries; Peera Hemarajata; Jeffrey D. Klausner (Emerging Infectious Diseases, 2017)
We investigated the epidemiology of the mutant gyrase A gene, a reliable predictor of ciprofloxacin resistance, in Neisseria gonorrhoeae infections at UCLA Health in Los Angeles, California, USA, during November 1, 2015–August 31, 2016. Among 110 patients with N. gonorrhoeae infections, 48 (44%) had the mutant gyrase A gene.